Ambiguity and Contestation in Legal Standing Restrictions: Rethinking Public Interest and Constitutional Rights in Indonesia - Arifin, Firdaus; Maarif, Ihsanul; Bahri, Robi Assadul; Suryana, Cece; Md. Nor, Mohd Zakhiri (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2025)
In Indonesia, the rules governing that can bring a legal case to the Constitutional Court often unclear and unevenly applied. This creates challenges for individuals and communities trying to protect their constitutional rights. In this article, we take a critical look at these obstacles by examining the Court’s past decisions. We show how the current legal framework overlooks issues of collective harm and structural inequalities, particularly affecting marginalized groups. To better understand these issues, we compare Indonesia’s approach to those of India, South Africa, and the United States, seeking out more inclusive models of judicial decision-making. Our findings show that Indonesia’s focus on specific interpretations of direct and personal harm limits the judiciary’s ability to meet its constitutional responsibilities. The paper draws on insights from other countries as well as Indonesia’s own legal traditions, such as adat (customary law) and musyawarah (deliberation), to propose a more inclusive and culturally sensitive approach to legal standing. We recommend several specific reforms, including rethinking existing laws, creating clearer judicial guidelines, and providing targeted judicial training for judges to improve access to constitutional justice for everyone.